2012
DOI: 10.1097/ccm.0b013e31825fd4d8
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, phased, cluster-randomized controlled trial to reduce central line-associated bloodstream infections in intensive care units*

Abstract: This study demonstrated a causal relationship between the multifaceted intervention and the reduced central line-associated bloodstream infections. Both groups decreased infection rates after implementation and sustained these results over time, replicating the results found in previous, pre-post studies of this multifaceted intervention and providing further evidence that most central line-associated bloodstream infections are preventable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 21 publications
3
114
0
3
Order By: Relevance
“…6 Yapılan çalışmalarla tam olarak sıfır enfeksiyon hedefi gerçekleştirile-mese de sıfıra yakın sonuçlar ortaya konmuş ve enfeksiyonla mücadele yöntemlerinin etkin olarak uygulanması ile katetere bağlı hastane enfeksiyonu oranlarının büyük oranlarda azaltıldığı açıkça belirtilmiştir. [7][8][9][10] Bu gelişmelerin yanı sıra turnikeler üzerinde yapılan kültür çalışmalarında, turnikelerin %34 oranında bakteriyel etkenler ile kontamine olması dikkat çekmiştir. 11 Sacar ve ark.nın çalışmasında; aynı çalışanlar üzerinde farkındalık oluşturulduğunda ve enfeksiyonla mücadele kurallarına uyulduğunda, turnikelerdeki metisilin rezistans Staphylococcus aureus ve MRKNS türleri gibi hastane enfeksiyonlarının sık rastlanan etkenlerinin turnikelerdeki kolonizasyonunun azaldığı gösterilmiştir.…”
Section: Discussionunclassified
“…6 Yapılan çalışmalarla tam olarak sıfır enfeksiyon hedefi gerçekleştirile-mese de sıfıra yakın sonuçlar ortaya konmuş ve enfeksiyonla mücadele yöntemlerinin etkin olarak uygulanması ile katetere bağlı hastane enfeksiyonu oranlarının büyük oranlarda azaltıldığı açıkça belirtilmiştir. [7][8][9][10] Bu gelişmelerin yanı sıra turnikeler üzerinde yapılan kültür çalışmalarında, turnikelerin %34 oranında bakteriyel etkenler ile kontamine olması dikkat çekmiştir. 11 Sacar ve ark.nın çalışmasında; aynı çalışanlar üzerinde farkındalık oluşturulduğunda ve enfeksiyonla mücadele kurallarına uyulduğunda, turnikelerdeki metisilin rezistans Staphylococcus aureus ve MRKNS türleri gibi hastane enfeksiyonlarının sık rastlanan etkenlerinin turnikelerdeki kolonizasyonunun azaldığı gösterilmiştir.…”
Section: Discussionunclassified
“…It was demonstrated in this study a causal relationship between the intervention and the reduction of ICS by CVC and sustained reduction after implementation of intervenção [7]. When we analysed the impact of an educational program on the prevention of infections associated with central venous catheters in paediatric intensive care units of university hospitals in our country it was concluded that a strategy focuses on the insertion and maintenance of venous access may decrease the infection rates associated with this acesso [8].…”
Section: Journal Of Intensive and Critical Care Issn 2471-8505mentioning
confidence: 99%
“…This study, in conjunction with other randomized trials using quality improvement techniques, 3 challenges the notion that quality improvement studies cannot be rigorous. This is important as we move beyond translation from bench to bedside, towards bedside to practice and populations.…”
mentioning
confidence: 96%